Strategi Pengelolaan Stres Guru Wanita Berstatus Guru Tetap Yayasan Sekolah Dasar Bersistem Full Day School - Dian Natalia Refti Farista (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: This study aims to: (1) describe the source of stress; (2) the way the female teacher remains a foundation teacher (GTY) manages stress; and (3) the way schools manage the stress of female teachers of GTY status. Data collection is by interview, observation, and documentation and then check its validity using data credibility, member checking, and peer discussion; dependability; transferability; and data conformability. The results of this study were: (1) the source of stress of GTY female teachers in both research sites stemmed from three things: biological consisting of physical illness; psychological consisting of life demands at work or at home, conflict with others; and socio-cultural, namely the tasks that come together, both at home and at work; (2) stress management strategies undertaken by female teachers of GTY status include: determining priority scale; support from family and friends; out of routine; organize diet and exercise; increase the intensity of worship; and (3) stress management strategies for female teachers of GTY status conducted by schools that include: daily arranging daily work schedule, upholding team strength, daily dialogue, reading at least 1 juz, meeting needs based on pyramid Maslow; weekly ie outdoor learning, study of religion, giving motivation to employees; monthly salary on time; per semester ie working meeting in tourist place, giving working index; and annual recreation with teachers and students, giving awards in the coronation of outstanding teachers. Abstrak: Penelitian ini bertujuan untuk: (1) mendeskripsikan sumber stres; (2) cara guru wanita berstatus guru tetap yayasan (GTY) mengelola stres; dan (3) cara sekolah mengelola stres guru wanita berstatus GTY. Pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi kemudian dicek keabsahannya menggunakan kredibilitas data, pengecekan anggota, dan diskusi teman sejawat; dependabilitas; transferabilitas; dan konfirmabilitas data. Hasil penelitian ini adalah: (1) sumber stres guru wanita berstatus GTY di kedua situs penelitian bersumber dari tiga hal, yaitu: biologis yang terdiri dari sakit fisik; psikologis yang terdiri dari tuntutan hidup di tempat kerja maupun di rumah, konflik dengan orang lain; dan sosial budaya, yaitu tugas-tugas yang datangnya bersamaan, baik di rumah maupun di tempat kerja; (2) strategi pengelolaan stres yang dilakukan oleh guru wanita berstatus GTY meliputi: menentukan skala prioritas; dukungan dari keluarga dan teman; keluar dari rutinitas; mengatur pola makan dan olahraga; meningkatkan intensitas ibadah; dan (3) strategi pengelolaan stres guru wanita berstatus GTY yang dilakukan oleh sekolah yaitu meliputi: harian yakni mengatur jadwal kerja harian, menjunjung tinggi kekuatan tim, dialog harian, membaca Al Quran minimal 1 juz, pemenuhan kebutuhan berdasarkan piramida Maslow; mingguan yakni outdoor learning, kajian ilmu agama, pemberian motivasi pada karyawan; bulanan yakni pemberian gaji tepat waktu; per-semester yakni rapat kerja di tempat wisata, pemberian indeks kerja; dan tahunan yakni rekreasi bersama guru dan siswa, pemberian penghargaan berupa penobatan guru-guru berprestasi.